An overview of engine durability and compatibility using biodiesel–bioethanol–diesel blends in compression-ignition engines. (15th November 2016) - Dharma, S.; Ong, Hwai Chyuan; Masjuki, H.H.; Sebayang, A.H.; Silitonga, A.S.
Graphical abstract: Highlights: The effects on engine performance and emission depend on biofuel properties. The engine performance can improve and emission reduces with biofuel as the fuel. Biofuel can ensure the long term engine durability and materials of diesel engine. Feasibility of biofuel carried out extended periods in corrosion behaviour. Biofuel appears to reduce life-cycle cost efficiencies for the alternative fuel. Abstract: The realization of declining fossil fuel supplies and the adverse impact of fossil fuels on the environment has accelerated research and development activities in renewable energy sources and technologies. Biofuels are renewable fuels made from edible, non-edible or waste oils, as well as animal fats and algae, and these fuels have been proven to be good substitutes for fossil fuels in the transportation sector. Bioethanol and biodiesels have gained worldwide attention in order to address environmental issues associated with fossil fuels, provide energy security, reduce imports and rural employment, as well as improve agricultural economy. Bioethanol has high oxygen content and octane content up to 35% and 108, respectively and hence, it increases oxygenation and improves combustion of fuel. In addition, bioethanol has lower vaporization pressure, which reduces the risks associated with evaporative emissions. In contrast, biodiesel has good lubricity, which helps protect the surface of engine components from wear and friction. The use of biodiesel–bioethanol–petroleum diesel blends poses a greater challenge with regards to improving the compatibility of the materials with the fuel system in compression ignition (CI) and spark ignition (SI) engines. In this work, the technical conditions of an engine ( i.e. engine deposits, wear of the engine components and quality of the lubrication oil) are assessed by the application of with biodiesel–bioethanol–petroleum diesel blends. It is deemed important to evaluate the effects of using bioethanol and biodiesels in diesel engines. This paper provides insight on the feasibility of biodiesel and bioethanol feedstocks, the compatibility of biodiesels, bioethanol and their blends with diesel engines as well as the physicochemical properties of these fuels.